The Effect of Social Environment and Organizational Culture on Employee Performance at The Social Services of West Sulawesi Province - Andi Achmad Syukri Tammalele; Mattalatta; Malik, Tajuddin (Journal of Indonesian Scholars for Social Research, 2022)
The Social Service of West Sulawesi Province has duties and functions in terms of formulating technical policies in the social sector following the Regional Development Plan (RPD), namely planning, fostering, and controlling technical procedures in the social sector, developing, fostering, and controlling technical policies for the implementation of the Technical Implementing Unit (TIU), and carrying out other tasks assigned by superiors following their field of duty. This type of research is descriptive qualitative research, where the data is in words and pictures, not numbers. Analysis of the data used is a descriptive-analytical method, describing the data collected in words, pictures, and not numbers. Data that comes from scripts, interviews, field notes, documents, and so on is then described so that it can provide clarity on reality or reality. In collecting this data, the authors go directly to the research object to obtain valid data. The results show that the relationship between elements of organizational culture is dynamic through a reciprocal process. Organizational values manifest basic assumptions and vice versa, so this process continues towards a balance point between stability and changing elements of the corporate culture. Performance quality is a result that can be measured by the effectiveness and efficiency of a job done by human resources or other resources in achieving the goals or objectives of the company properly and efficiently.